2008
DOI: 10.1017/s002211200800308x
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic forcing of the Lamb–Oseen vortex

Abstract: The aim of the present paper is to analyse the dynamics of the Lamb–Oseen vortex when continuously forced by a random excitation. Stochastic forcing is classically used to mimic external perturbations in realistic configurations, such as variations of atmospheric conditions, weak compressibility effects, wing-generated turbulence injected into aircraft wakes, or free-stream turbulence in wind tunnel experiments. The linear response of the Lamb–Oseen vortex to stochastic forcing can be decomposed in relation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…They found qualitative agreement between the two, further supported by recent results of HPS showing that the dominant core perturbation is a bending wave mode (at k ≈ 1.4, the peak k value predicted from linear analysis). This is further supported by Fontane, Brancher & Fabre (2008), who found that stochastic forcing of the Oseen vortex also excited large growth at m = 1, k = 1.4. Dominance of m = 1 is expected as turbulence could simultaneously excite multiple transiently growing perturbations, with m = 1 being the most unstable.…”
Section: Transient Growth In Turbulent Vorticessupporting
confidence: 63%
“…They found qualitative agreement between the two, further supported by recent results of HPS showing that the dominant core perturbation is a bending wave mode (at k ≈ 1.4, the peak k value predicted from linear analysis). This is further supported by Fontane, Brancher & Fabre (2008), who found that stochastic forcing of the Oseen vortex also excited large growth at m = 1, k = 1.4. Dominance of m = 1 is expected as turbulence could simultaneously excite multiple transiently growing perturbations, with m = 1 being the most unstable.…”
Section: Transient Growth In Turbulent Vorticessupporting
confidence: 63%
“…The same trend was observed by Devenport et al (1996), who used hot-wire anemometry to estimate the amplitude of the lateral motion of a single trailing vortex, the so-called vortex meandering (Roy & Leweke 2008). This phenomenon is currently not fully understood; a probable explanation is related to transient growth of perturbations triggered by random external perturbations (Antkowiak & Brancher 2004;Fontane, Brancher & Fabre 2008;Roy & Leweke 2008), which can either come from the turbulence of the free stream, or be generated in the wake of the wing, possibly through flow separation at the relatively low Reynolds numbers considered here. The development of the Crow instability is the second factor leading to an increase of a M and a m , as the amplitude of the long sinusoidal deformations of the vortices increases.…”
Section: Three-dimensional Base Flowmentioning
confidence: 95%
“…We assume that F is a unitary matrix (F † F = I) so that its columns are orthogonal; the forcing is defined as the sum of an orthonormal set of uncorrelated processes. As mentioned by Fontane et al (2008), a spatial covariance matrix representing a true experimental noise environment may also be used in order to represent more specific perturbation fields. In our case, we assume that no information on the noise is available and keep the above-mentioned formulation so as to mimic the most generic unknown disturbances in an unbiased manner.…”
Section: Empirical Orthogonal Functionsmentioning
confidence: 99%
“…These are referred to as stochastic optimals (SOs), see Farrell & Ioannou (1993a,b, 2001. The stochastic forcing approach has been successfully applied in systems with a small number of degrees of freedom by Fontane, Brancher & Fabre (2008). Our goal is to show how these quantities may be computed for high dimensional fluid systems and how these structures (EOFs and SOs) may be related to the instabilities displayed by the system (optimal perturbations or optimal forcing responses).…”
Section: Introductionmentioning
confidence: 99%